The effect of macrolides on the growth of macrophytes - Aubakirova, B.N.; Beisenova, R.R.; Rakhymzhankyzy, Zh.; Zhurmanova, N.Sh. (Fundamental and Experimental Biology, 2018)
The present research is highly relevant and considers the problem of the ecotoxicity of pharmaceuticals that are persistent in the environment. Until recently, pharmaceuticals have never been studied as chemical pollutants in Kazakhstan. Pharmaceuticals can have toxic effect to the environmental organisms even in low concentration. Their concentrations were determined in surface waters around the Earth. It is important to conduct the study of the toxicity of antibiotics to the aquatic organisms. The following study demonstrates the results ecotoxicological experiment on duckweed Lemna minor. Macrolides as azithromycin and clarithromycin were selected for toxicity test of macrophyte. The test concentrations of substances were set up as 10, 30, 50, 70 and 100 mg/L. The effect of drugs on study species were assessed based on two measurement variables as frond numbers and total frond areas. The results of the research showed that Lemna minoris sensitive to the exposure of macrolides even in low concentration. Total growth inhibition was found in concentration 70 mg/L of azithromycin, while clarithromycin showed 100 % inhibition of duckweed in concentration 50 mg/L.